Tissue‐resident regulatory T cells accumulate at human barrier lymphoid organs. Issue 8 (27th July 2021) - Hewavisenti, Rehana V; Ferguson, Angela L; Gasparini, Georgia; Ohashi, Tomoki; Braun, Asolina; Watkins, Thomas S; Miles, John J; Elliott, Michael; Sierro, Frederic; Feng, Carl G; Britton, Warwick J; Gebhardt, Thomas; et al.
Abstract: Regulatory T cells (Tregs) play a critical role in immune regulation and peripheral tolerance. While different types of Tregs have been identified in both mice and humans, much of our understanding about how these cells maintain immune homeostasis is derived from animal models. In this study, we examined two distinct human lymphoid organs to understand how repeated exposure to infections at the mucosal surface influences the phenotype and tissue localization of Tregs. We show that while Tregs in both tonsils and spleen express a tissue‐resident phenotype, they accumulate in greater numbers in tonsils. Tonsillar‐resident Tregs exhibit a highly suppressive phenotype with significantly increased expression of CD39, ICOS and CTLA‐4 compared with their counterparts in circulation or in the spleen. Functionally, resident Tregs are able effectively to suppress T cell proliferation. We further demonstrate that tonsillar‐resident Tregs share key features of T follicular helper cells. Spatial analysis reveals that the vast majority of resident Tregs are localized at the border of the T‐zone and B cell follicle, as well as within the lymphocyte pockets enriched with resident memory T cells. Together our findings suggest that resident Tregs are strategically co‐localized to maintain immune homeostasis at sites of recurrent inflammation. Abstract : Here we show that tissue‐resident regulatory T cells could play a key role in maintaining tissue homeostasis, which in turn could be critical for mucosal sites that are exposed to regular challenges.